Pendeteksi Gerakan Menggunakan Sensor PIR untuk Sistem Keamanan di Ruang Kamar Berbasis SMS - Ruuhwan Ruuhwan; Randi Rizal; Rizal Kurniawan (Teknik Informatika Universitas Pamulang, 2020)
Room safety is very important considering that the crime scene is very disturbing to the public, one of which is the usual theft case. This might be caused partly because of economic factors that cause people to sometimes take shortcuts to make ends meet by stealing. So the PIR sensor sensor tool was made to detect human movements making it easier for us to control security when leaving a room empty, the media used is Mobile, by utilizing SMS facilities. The purpose of this research is the implementation of the PIR sensor as a detector of human motion in a room based on sms. This tool consists of a sensor that is a pir sensor as a detector of human motion around, and the bazzer will sound every time there is a movement that is captured by a pir sensor, a GPRS Shield which has a sim card inside that works to send SMS. This type of research used is qualitative research with experimental methods, namely by conducting a cona test (trial and error) for mechanical and electronic design components of the hadware and trying to explain. From this research produced information provider using two KC7738 PIR-based SMS sensors can be applied by the public so that they can provide information when leaving a room empty.